Creating safe, inclusive spaces for hospital-based health care staff and people who use drugs: an exploratory qualitative study in Vancouver, Canada - Aaron Bailey; Elizabeth Bishop; Agnes T. Black; Elizabeth Dogherty; George Sedore; Marge Humchitt; John Onland; Jane Milina; Varun Bangar; Heather Mackie; Herb Varley; Tyler Byrd; et al. (Harm Reduction Journal)
Abstract Objectives This project sought to contribute to healthy, safe organizational cultures within Vancouver’s hospital system healthcare system as one method to address indirect harms of the province’s drug toxicity and housing syndemic. A tertiary care inner-city hospital in western Canada partnered with the Eastside Illicit Drinkers Group for Education and Vancouver Area Network of Drug Users to convene a participatory action research project to identify systemic and personal barriers to safe, non-stigmatizing, and effective care at a local health care setting and to propose ways of responding to these conditions. Methods We convened semi-structured Listening Circles held in October 2023 with people who have sought care at the urban health care setting, and frontline healthcare workers who respond to them. The Listening Circles included a graphic recorder who illustrated themes as participants spoke about their experiences, perceived barriers to safety and comfort in health care settings, and challenges faced by service providers and service users when interacting with one another. Results Common themes identified by a graphic recorder included: (1) the importance of time and in the absence of time, relational space between healthcare workers and people who use drugs, (2) shared desire to scale approaches like peer navigation which consider the wellbeing of both service recipients and providers, and (3) the role of systemic forces and organizational practices that obstruct both quality of care and healthcare worker wellbeing. Conclusions Healthcare workers and people who use drugs and alcohol report an urgent need for resourced, relational care spaces and peer advocates within their area hospital systems. We will use these themes to inform our next steps in an investigation-as-action effort to improve respect, safety, and equity for all stakeholders across multiple stages of care.